Creative Accounting Model for Increasing Banking Industries’ Competitive Advantage in Indonesia - Supriyati, Supriyati; Herlina, Erida (International Research Journal of Business Studies, 2015)
Bank Indonesia demands that the national banks should improve their transparency of financial condition and performance for public in line with the development of their products and activities. Furthermore, the banks’ financial statements of Bank Indonesia have become the basis for determining the status of their soundness. In fact, they tend to practice earnings management in order that they can meet the criteria required by Bank Indonesia. For internal purposes, the initiative of earning management has a positive impact on the performance of management. However, for the users of financial statements, it may differ, for example for the value of company, length of time the financial audit, and other aspects of tax evasion by the banks. This study tries to find out 1) the effect of GCG on Earnings Management, 2) the effect of earning management on Company value, the Audit Report Lag, and Taxation, and 3) the effect of Audit Report Lag on Corporate Value and Taxation. This is a quantitative research with the data collected from the bank financial statements, GCG implementation report, and the banks’ annual reports of 2003-2013. There were 41 banks taken using purposive sampling, as listed on the Indonesia Stock Exchange. The results showed that the implementation of GCG affects the occurrence of earning management. Accounting policy flexibility through earning management is expected to affect the length of the audit process and the accuracy of the financial statements presentation on public side. This research is expected to provide managerial implications in order to consider the possibility of earnings management practices in the banking industry. In the long term, earning management is expected to improve the banks’ competitiveness through an increase in the value of the company. Explicitly, earning management also affects the tax avoidance; therefore, the banks intend to pay lower taxes without breaking the existing legislation Taxation Provisions.